Newnes PC troubleshooting pocket book - Anderson, Howard; Tooley, Michael H. (Oxford ; Burlington, MA : Newnes, 2003)
Newnes PC Troubleshooting Pocket Book provides a concise and compact reference that describes, in a clear and straightforward manner, the principles and practice of faultfinding and upgrading PCs and peripherals. The strong practical emphasis is backed up with many illustrations and examples of real-lie problems. The book is aimed at anyone who is involved with the installation, configuration, maintenance, upgrading, repair or support of PC systems. It also provides non-technical users with sufficient background information, charts and checklists to enable the diagnosis of faults and help to carry out simple modifications and repairs. The new edition of PC Troubleshooting will continue to include a number of short cuts that are instrumental in avoiding hours of potential frustration and costly effort. In order to reflect rapid changes in computer technology (both hardware and software) this new edition has been completely revised and rewritten. New and expanded sections on: modern machines (Pentium II, III, IV, AMD); modern buses (FSB, AGP, Cyrix, Chip sets); different RAM chip types and connectors; Win 2000, ME, XP; latest SCSI standards, Ultra DMA, "live" re-partitioning of the disc, FAT16, FAT36, NTFS, performance and compatibility differences; 'famous' viruses and personal firewalls. * All the essential data for PC fault-finding and upgrading * Ideal for systems support staff, businesses, students, teachers, and home PC users * Strong practical emphasis is backed up with many illustrations and examples of real problems.
Introduction -- The Internet -- Microcomputer fundamentals -- System architecture and construction -- The PC expansion buses -- Semiconductor memory -- Printers and the printer interface -- The serial communication ports -- Replaceable disk drives -- Hard disk drives -- Displays -- Viruses -- Troubleshooting Windows error messages -- Troubleshooting Windows registry.
Includes index.
Keywords: Microcomputers -- Maintenance and repair -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc